Structural analysis of ethanol extract of the stem of Brunfelsia grandiflora D. Don and its neuropathological effect on rat cerebellum - Castro L, Américo J (2012)
The objective of the study was to elucidate the structure of the etanólic extract of the stem of Brunfelsia grandiflora D. Don and to evaluate its citotoxicity and the neuropathological effect on rat cerebellum. Obtained the extract the structural elucidation was made by Gas Chromatography/was made /Espectrometría of Masa (CG/EM), identifying the chemical components: Etil ester of vainíllic, octacosano, octadecan acid, palmític acid, 7 hidroxi-6-metoxi-cumarin, linoleate of ethyl and linoleic acid. The cytotoxic analysis was evaluated in embryos of Tetrapygus Niger black sea urchin, applying different concentrations of the extract. The evaluation of the neuropatológic effect of the etanólic extract in the rat cerebellum was made in 30 albino rats, Holtzmann strain, male stock, with corporal weight average of 250g approximately. For the study of the neuropatológic effect were administered concentrations of 7,5 and 15 mg/mL of the extract. Were observed diminution and deformation of the neurons with protoplasm disoriented, vacuolated and necrotic; with great nuclei and deformed and others without nucleus, anisocitosis and poiquilocitosis. Was concluded that the etanólic extract of the stem of the studied species, has neuropatológic effect in the rat cerebellum. This investigation was based on the study of the drug and its neuropatológic effect that affects to deep cerebelar nucleus and motor coordination of the bacteriological agents used. Keywords: Brunfelsia grandiflora D. Don, cytotoxicity, neuropathological, Gas Chromatography / Mass Spectrometry (GC / MS).